Cost-effectiveness analysis of drug-eluting beads and conventional transarterial chemoembolization in the treatment of hepatocellular carcinoma - Shao, Guoliang; Wang, Jingwen; Zhou, Xiaoying; Sun, Guojun; Dong, Zuojun (Frontiers in Public Health, 2022)
Objective: To conduct a cost-effectiveness analysis of drug-eluting beads transcatheter arterial chemoembolization (DEB-TACE) and conventional transcatheter arterial chemoembolization (cTACE) for first-line treatment of hepatocellular carcinoma (HCC) from the perspective of the Chinese healthcare system. Methods: Based on the real-world clinical data of HCC patients receiving interventional therapy, a partitioned survival model was constructed for cost-effectiveness analysis. The model period is one month, and the research time limit is 10 years. The incremental cost-effectiveness ratio (ICER) is used as the evaluation index. One-way sensitivity analysis and probabilistic sensitivity analysis were used to analyze the uncertainty of parameters to test the stability of the model results. Results: The ICER of the DEB-TACE group was 11875.62 /QALYs, which was lower than the willingness to pay threshold (WTP) of 31499.23 /QALYs. One-way sensitivity analysis suggested that the utility value of progression-free survival (PFS) in the DEB-TACE group had the greatest impact. Probabilistic sensitivity analysis showed that at the level of WTP of 31499.23 /QALYs, DEB-TACE had a cost-effective probability of 92%. Conclusion: Under the current economic level in my country, DEB-TACE is more cost-effective than cTACE in the treatment of HCC patients.